Manipulation of interactions at membrane interfaces for energy and environmental applications. (May 2018) - Zhao, Jing; He, Guangwei; Liu, Guanhua; Pan, Fusheng; Wu, Hong; Jin, Wanqin; Jiang, Zhongyi
Abstract: Synthetic membranes play an increasingly critical role in various energy and environment-related applications such as carbon capture and water purification. Owing to the great promise in solving the permeability/selectivity trade-off and the separation performance/stability trade-off, heterogeneous membranes primarily including mixed matrix membranes and composite membranes have become a prevalent membrane configuration in various membrane processes. For heterogeneous membranes, interfacial interaction is an essential factor, which governs the nano-/molecular-scale assembly of membrane materials, tunes the hierarchical structures and enhances the comprehensive properties of membranes. This review highlights the recent advances in manipulating interfacial interactions of heterogeneous membranes with the focus on two kinds of typical interfaces: the separation layer-support layer interface in composite membranes and the polymer matrix-filler interface in mixed matrix membranes. Common methods for interfacial interactions manipulation of heterogeneous membranes are extensively summarized. The applications of manipulating interactions at membrane interfaces in energy and environment-related realms are briefly introduced. Finally, the future directions of manipulating interfacial interactions of heterogeneous membranes are tentatively identified.